Analisis Kuat Geser Perekat Alami Berbahan Soy Protein Isolate dengan Variasi Natrium Sulfit dan Asam Oksalat - Koesman, Steven; Budhijanto; Bennet, David; Pancasakti, Bima (Jurnal Teknik Kimia USU, 2023)
Along with the technology development, the use of bioadhesive for medical purpose is a common thing.Â The purpose of this bioadhesive is to give support for the medication because it can be decomposed and ejected by human body. This research aims to analyze the quality of bioadhesive made of soy protein isolate (SPI) as main ingredient. SPI has food-grade level of safety thus it is safe for human body. This bioadhesive is made by two main processes: denaturation of protein dan acid crosslinking. The processes are done under condition of 55 Â°C dan atmospheric pressure for 30 minutes dan 10 minutes. Shear strength, wet shear strength, viscosity, solid content, and fourier transform infrared spectroscopy (FTIR) analysis were done to find out the impact of oxalic acid addition. The best shear strength result obtained was 1.9051 MPa and wet shear strength result was 1.6093 MPa.